1997
DOI: 10.1046/j.1365-2958.1997.4231796.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis of the phage λ CII regulatory protein by FtsH (HflB) of Escherichia coli

Abstract: SummaryRapid proteolysis plays an important role in regulation of gene expression. Proteolysis of the phage CII transcriptional activator plays a key role in the lysis-lysogeny decision by phage . Here we demonstrate that the E. coli ATP-dependent protease FtsH, the product of the host ftsH/hflB gene, is responsible for the rapid proteolysis of the CII protein. FtsH was found previously to degrade the heat-shock transcription factor 32 . Proteolysis of 32 requires, in vivo, the presence of the DnaK-DnaJ-GrpE c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
122
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(126 citation statements)
references
References 41 publications
4
122
0
Order By: Relevance
“…Previous work has shown that E. coli FtsH can tolerate the addition of an affinity tag at the C terminus (Akiyama et al, 1995;Shotland et al, 1997). Consequently, to aid the purification of FtsH2, we constructed a strain of Synechocystis 6803, termed SynFtsH2GST, in which a GST affinity tag that also included a C-terminal Strep II tag, was fused to the C terminus of FtsH2 (see Methods).…”
Section: Phenotype Of a Gst-tagged Ftsh2 Derivative Of Synechocystis mentioning
confidence: 99%
“…Previous work has shown that E. coli FtsH can tolerate the addition of an affinity tag at the C terminus (Akiyama et al, 1995;Shotland et al, 1997). Consequently, to aid the purification of FtsH2, we constructed a strain of Synechocystis 6803, termed SynFtsH2GST, in which a GST affinity tag that also included a C-terminal Strep II tag, was fused to the C terminus of FtsH2 (see Methods).…”
Section: Phenotype Of a Gst-tagged Ftsh2 Derivative Of Synechocystis mentioning
confidence: 99%
“…1c, d). FtsH contributes to the activation of the lytic cycle of phage l in E. coli by regulating the levels of the transcription factor CII and Xis (Shotland et al, 1997;Leffers & Gottesman, 1998). Thus, a probable scenario could be that TP712 gets locked in the lysogenic state in L. lactis DftsH because the ftsH mutation inhibits prophage activation or replication of the TP712 DNA.…”
mentioning
confidence: 99%
“…In the simplest model, the proteases catalyze unfolding by pulling at the polypeptide chain, perhaps simply as a consequence of the translocation of the polypeptide chain into the degradation channel [1]. Once the protein reaches the proteolytic sites, it is hydrolysed into 3-30 amino acids-long peptides [7,8] (Figure 2). …”
mentioning
confidence: 99%